Efficacy and safety of topical SR-T100 gel in treating actinic keratosis in Taiwan: A Phase III randomized double-blind vehicle-controlled parallel trial. Issue 3 (June 2018) - Yang, Chao-Chun; Wong, Tak-Wah; Lee, Chih-Hung; Hong, Chien-Hui; Chang, Chung-Hsing; Lai, Feng-Jie; Lin, Shang-Hung; Chi, Ching-Chi; Lin, Tzu-Kai; Yen, Hsi; Wu, Chin-Han; Sheu, Hamm-Ming; et al.
Highlights: Current topical treatments to actinic keratosis have substantial side effects. Topical SR-T100 gel yielded 32.4% complete clearance rate and 71.8% partial clearance rate to AK lesions. Topical SR-T100 gel may be a safe and effective treatment modality for field therapy of actinic keratosis. Abstract: Background: Currently available topical treatments for actinic keratosis (AK) are associated with substantial side-effects. Objectives: To evaluate the efficacy and safety of topical SR-T100 gel in treating AK. Methods: A multicenter, randomized, double-blinded phase III trial was conducted. Patients with at least two clinically visible AK were enrolled and a punch biopsy was performed on one of the AK to confirm the diagnosis. This study consisted of up to 16-week treatment and 8-week post-treatment periods. Medication was applied daily with occlusive dressing. Results: 123 subjects were recruited and 113 were randomized. 76 subjects were in the SR-T100 and 37 in the vehicle arms. In SR-T100 and vehicle groups, 32.39% and 17.14% of subjects achieved complete clearance, respectively. For 75% partial clearance of lesions, 71.83% and 37.1% of subjects achieved this goal in SR-T100 and vehicle group, respectively. When comparing SR-T100 to vehicle, the odds ratio of complete clearance was 2.14 ( p   =  0.111), and odds ratio of partial clearance was 4.36 ( p  < 0.001). Severe local reactions were reported by only one subject using SR-T100. Conclusion: The imitation of the study was that not all the treated AK lesions were confirmed by histopathology. The diagnostic uncertainty may contribute to the high partial clearance rate in the vehicle group since the clinical-diagnosed AK showed higher clearance rate compared to histopathology-confirmed AK. The use of occlusive dressing was another possible explanation for high placebo effects. The results suggested that topical SR-T100 gel may be an effective and safe treatment for field therapy of AK.